An Introduction To Digital Cash World - Dewi, Lusiana Citra (Bina Nusantara University, 2010)
Digital cash is one of the payment methods that is very easy to use, especially when someone is doing a transaction through the internet. Digital cash has many forms and systems, which are supposed to simplify and make the process of transaction easier. This paper will discuss about the definition of the digital cash itself, the important properties that it has, the problems which occur due to its existence, the examples of some key players who operate the digital cash from all around the world, along with how the digital cash works, and lastly, how the digital cash is put into the practical world. The purpose of this paper is to give a glimpse of view on the functions of the digital cash, the systems or protocols which are needed to implement it, and the problems faced by those who use it.